Cerebral Palsy Clinical and Therapeutic Aspects - Jaber Al-Zwaini, Isam (IntechOpen, 2018)
Cerebral palsy is a common pediatric problem and is the leading cause of childhood disability. It occurs at a rate of 3.6 cases per 1000 children, and represents a major social and psychological impact on both family and society. It is a group of disorders with movement difficulties being common for all affected patients. Its severity and extent are variable from one patient to another. Additionally, the impacts of cerebral palsy on daily activities, communications, and requirements are also variable. Recent advances in clinical research increase our knowledge and understanding of causal pathways, possible preventive measures, specific intervention strategies, and the value of new treatment modalities such as botulinum toxin and intrathecal baclofen in the management of cerebral palsy.